A Case of Drug Dependence Syndrome to Baclofen Following High-Dose Therapy - Sénécal, Léa Hamel; Chrétien, Basile; Jean-Jacques, Pierre-Yves; Boulouard, Véronique Lelong; Cohen, Daniel; Boisselier, Reynald Le (Journal of Clinical Psychopharmacology, 2018)
Hamel Sénécal, Léa PharmD; Chrétien, Basile PharmD; Jean-Jacques, Pierre-Yves MD; Lelong Boulouard, Véronique PharmD, PhD; Cohen, Daniel MD; Le Boisselier, Reynald PharmD Author Information